2013
DOI: 10.1111/jvs.12094
|View full text |Cite
|
Sign up to set email alerts
|

Post‐fire recovery of desert bryophyte communities: effects of fires and propagule soil banks

Abstract: Questions As changing wildfire regimes modify North American deserts, can fires of greater severity and frequency negatively impact the recovery of native bryophyte communities, which are not adapted to such disturbances? Does post‐fire recovery result from the survival of existing surface plants, dormant propagules in sub‐surface soil banks (dispersal in time) or aerial immigration into burned sites (dispersal in space)? Do wildfires negatively affect the survival of propagules in bryophyte soil banks? Locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Change in bryophyte species composition after the fire also follows the general model due to the environmental post-fire conditions with an increase in the frequency of acrocarpous species in burned soil and pleurocarpous in unburned soil [138][139][140]. The high frequency of cosmopolitan moss Funaria hygrometrica in the burned ground, mainly those affected by high intensity fire, is in accordance with several previous studies on post-fire bryophyte dynamics in the Mediterranean vegetation [140][141][142][143].…”
Section: Fire Effect On Vascular Plants and Bryophyte Diversitysupporting
confidence: 88%
“…Change in bryophyte species composition after the fire also follows the general model due to the environmental post-fire conditions with an increase in the frequency of acrocarpous species in burned soil and pleurocarpous in unburned soil [138][139][140]. The high frequency of cosmopolitan moss Funaria hygrometrica in the burned ground, mainly those affected by high intensity fire, is in accordance with several previous studies on post-fire bryophyte dynamics in the Mediterranean vegetation [140][141][142][143].…”
Section: Fire Effect On Vascular Plants and Bryophyte Diversitysupporting
confidence: 88%
“…Although the exact mechanism is uncertain, at least one study has provided an example of regeneration from spore banks after fire in a North American desert community (Smith et al, 2014). Studies investigating post-fire succession often find a rather slow return of the pre-fire bryophyte species composition.…”
Section: Introductionmentioning
confidence: 99%
“…We found similar beta diversity patterns in these two archipelagos, indicating that the time since isolation is longer enough than the time needed for the successful colonization of bryophytes, that is,~30 yr (Smith et al 2014, Jagodzi nski et al 2018. Thus, we cannot conclude that isolation time has no effect on species composition of bryophyte communities, unless assessing more natural archipelagos with a larger range of isolation time (especially those newly formed archipelagos), or conducting experiments to manually control the effect of isolation time.…”
Section: Uncertainties and Limitationsmentioning
confidence: 81%
“…Highlighting this ability, Hutsemekers et al (2008) found that for 56% of bryophyte species, recruits dispersed at least 6–86 km from source populations in <50 yr. In previous studies, bryophyte communities have been found to restore successfully within ~30 yr after catastrophic disturbance (e.g., wildfire; Smith et al 2014, Jagodziński et al 2018). In contrast, Pharo et al (2004) found evidence for lower richness and shifts in species composition in newly formed fragments (<25 yr) compared to near contiguous habitats, suggesting that some species with weaker dispersal ability may exhibit greater time lag between colonization events.…”
Section: Discussionmentioning
confidence: 96%